FROM THE ‘RICEBOWL OF MALAYSIA’ TO EXOTIC CUISINES: IMAGINATION OF KEDAH BY DESTINATION MARKETERS - Norhanim Abdul Razak (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The state tourism officials have continuously promoted places of interest and attractions within Kedah even during the enforcement of MCO in Malaysia. The ongoing marketing effort is worthwhile as potential tourists can plan and choose the places they would like to visit after the lockdown has been lifted. Hence, it is vital to evaluate the current promotion of Kedah as a tourist destination as marketing plays a crucial role in enhancing the appeal of a particular site and attracting tourists. Firstly, this paper investigates how the state of Kedah has been marketed by the national and state tourism promotional bodies. Additionally, the portrayals of Kedah by international travel organizations were also examined. The semiotic analysis method was employed in the assessment, where it focused on how Kedah has been presented on the websites of these organizations. In general, the findings of this paper uncovered several prominent visual and textual signifiers showing and describing field fields on the websites of both national and state promotional organizations. The attraction points such as Paddy Museum, Zahir Mosque, Balai Nobat, Mahathir’s Birth Place, and Pekan Rabu have been featured strongly in portraying the capital city, Alor Setar. The signified meanings of the uniqueness and exoticism of local cuisines are reflected through visual and textual signifiers, including laksa Kedah, pekasam (fermented fish), and traditional snacks such as kuih dangai and kuih karas. As Kedah is popularly known as the ‘Rice Bowl of Malaysia’, it is reasonable that visual and textual signifiers of paddy fields and attractions associated with paddy have been presented widely on the websites. Overall, the key theme in marketing Kedah as a tourist destination via public and private travel promotional websites is reflected as the projection of cultural-rural tourism.